The Effectiveness of Tour Leaders' Interpersonal Skills with Tourists (A Case Study of Cakrawala Perdana Tour and Travel) - Kirei Shakira Lanora Tinanie; Farida Nurfalah (Journal of World Science, 2026)
Interpersonal communication is a key factor in determining service quality in the tourism industry, particularly in interactions between tour leaders and tourists, as it contributes to tourists’ sense of security, comfort, and emotional connection. However, these interactions often encounter various challenges, including tourists’ reluctance to express complaints, misunderstandings of information, and situational pressures during tours. This study aimed to evaluate the effectiveness of interpersonal communication between tour leaders and tourists at Cakrawala Perdana Tour and Travel and to identify barriers encountered during the communication process. Using a qualitative case study design, data were collected through in-depth interviews with two tour leaders as primary informants and two tourists as supporting informants. The data were analyzed using the Miles and Huberman interactive model and DeVito’s five dimensions of interpersonal communication effectiveness: openness, empathy, supportiveness, positiveness, and equality. The findings indicated that effective interpersonal communication was demonstrated through clear information delivery, attentiveness to tourists’ feelings, the creation of a sense of security, consistently friendly interactions, and equitable and participatory treatment. The identified communication barriers included tourists’ reluctance to express complaints, misunderstandings arising from sudden schedule changes, difficulties in recognizing tourists’ emotions in crowded situations, time constraints, emotional pressure, and the dominance of certain participants in group interactions. To overcome these barriers, tour leaders employed several communication strategies, including the use of digital communication channels, emotional validation, personalized communication approaches, and priority setting.